2011
DOI: 10.1371/journal.pone.0024430
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Leaf Symbiosis in Angiosperms: Host Specificity without Co-Speciation

Abstract: Bacterial leaf symbiosis is a unique and intimate interaction between bacteria and flowering plants, in which endosymbionts are organized in specialized leaf structures. Previously, bacterial leaf symbiosis has been described as a cyclic and obligate interaction in which the endosymbionts are vertically transmitted between plant generations and lack autonomous growth. Theoretically this allows for co-speciation between leaf nodulated plants and their endosymbionts. We sequenced the nodulated Burkholderia endos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
81
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 170 publications
(90 citation statements)
references
References 80 publications
(88 reference statements)
6
81
3
Order By: Relevance
“…A previous study (13), however, rejected a history of strict cospeciation in leaf-nodulated Psychotria species and suggested a recent shift toward a host-specific association and ongoing cospeciation. To test this hypothesis, we analyzed a five-gene endosymbiont and twogene host data set, including 15 and 8 lineages and populations of Psychotria leptophylla, respectively.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…A previous study (13), however, rejected a history of strict cospeciation in leaf-nodulated Psychotria species and suggested a recent shift toward a host-specific association and ongoing cospeciation. To test this hypothesis, we analyzed a five-gene endosymbiont and twogene host data set, including 15 and 8 lineages and populations of Psychotria leptophylla, respectively.…”
mentioning
confidence: 85%
“…Recent studies using culture-independent PCR methods revealed the identity of the endophytes of all leaf-nodulated plants as Burkholderia (10)(11)(12)24). More interestingly, it was also demonstrated that high host specificity occurs as a result of vertical symbiont transfer and that frequent host switches are observed, rejecting a long-term cospeciation (13). These results suggest a diffuse bacterium-plant interaction as an ancestral state of bacterial leaf symbiosis, followed by an evolution toward a more specific one-to-one interaction, where the bacterial associate became an obligate and vertically inherited endosymbiont of the host.…”
mentioning
confidence: 99%
See 3 more Smart Citations